Functional outcome of intertrochanteric fractures treated with bipolar hemiarthroplasty - Kadam, Rahul; Sawant, Ritesh; Chhallani, Abhay (International Journal of Research in Orthopaedics, 2016)
Background: Comminuted intertrochanteric fractures with severe displacement are common in elderly patients. These patients have poor bone quality and conventional osteosynthetic procedures frequently lead to non-union and metal failure. The primary goals of treatment are stable fixation and early rehabilitation. There are a many treatment for intertrochanteric fractures but our study is on unstable intertrochanteric fractures which are challenging for a surgeon. The aim of this study was to evaluate the results of cemented bipolar hemiarthroplasty as an alternative to other treatment modalities such as DHS or PFN. 21 elderly patients with comminuted and unstable intertrochanteric fractures underwent cemented bipolar hemiarthroplasty. Methods: This study includes 22 cases of intratrochantric fracture. Mean age of patients was 73.3 (range 60 - 91). All patients are treated with bipolar hemiarthoplasty. Patients are followed up for a mean period of 6 months (range 3-9 months). Results: These patients were evaluated using the Harris hip scoring system. 21 out of 22 had excellent to fair outcomes. Conclusions: In our study of 22 patients, 21 had excellent to fair outcomes with primary cemented bipolar hemiarthroplasty. Bipolar hemiarthoplasty offers good functional outcome and early weight bearing and mobilization.